Isolation and characterization of Bacteriophages from surface water specific for Vibrio Cholerae - Priyanka, Farzana Mansur (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2020.